Chemical Constituents of Tetradium sambucinum (Bl.) Hartley - Ismiarni, Komala; Rahmani, Mawardi; G.C.L, Ee; Mohd Ismail, Hazar Bebe; Sukari, Mohd Aspollah; Rahmat, Asmah (Malaysian Journal of Science, 2006)
Detailed extraction and separation of the aerial parts of Tetradium sambucinum (Bl.) Hartley have led to the isolation of decarine, rutaecarpine, aurantiamide acetate and 7-hydroxycoumarin. The structures of the compounds were established by one and two-dimensional ¹H- and ¹³C-NMR as well other spectroscopic methods. The free radical scavenging and cytotoxic activities were assessed by DPPH assay and against two cancer cell lines, respectively.